DETERMINATION OF PERMISSIBLE SPEEDS OF FREIGHT CARS ON RAILROAD TRACKS 1520 MM - Danovych, V. D.; Rybkin, V. V.; Myamlin, S. V.; Reidemeister, O. H.; Triakin, A. P.; Khalipova, N. V. (Science and Transport Progress, 2003)
The article is devoted to questions of the admitted speeds establishment of various tipes of freight 4 axis cars movement with carriages 18-100 (ЦНИИ-Х3), in empty and full a condition. The results of the complex researches of dynamic qualities of the cars are given and their influence on a track is appreciated. As a result of researches it is offered to establish different the approach to an establishment of admitted speeds of movement for empty and full cars.